Genomic and cellular contributions to establish the fish Hyphessobrycon heterorhabdus as an Amazonian model for ecotoxicology - Cardoso, Adauto Lima [UNESP]; Moreira, Camila do Nascimento [UNESP]; Nascimento, Yure Jefferson da Cruz do; Frade, Luan Felipe da Silva; Noronha, Renata Coelho Rodrigues; Amado, Lílian Lund; Martins, Cesar [UNESP] (Oxford University Press (OUP), 2025)
The Amazon has environmental characteristics that make it unique, and the species that inhabit it have physiological features that demonstrate their adaptation to an Amazonian context. Amazonian ecosystems have been undergoing transformations that result from inadequate human actions, which have placed biodiversity at the limits of their biological abilities. Therefore, it is essential to identify organisms that reflect the conditions of the Amazon environment, considering the physiology of these species, and that they are established as bioindicators for this region. The fish Hyphessobrycon heterorhabdus is distributed throughout the lower and middle Amazon basin. Aiming to contribute to the establishment of this species as a bioindicator, we carried out for the first time its karyotyping, Illumina sequencing and assembly of the nuclear genome and mitogenome, in addition to establishing a cell line for this species. Individuals of H. heterorhabdus have 48 chromosomes, a number that is held in the cell line. Sequencing and genomic assembly generated a draft genome that is useful for recovering species-specific coding and regulatory genomic sequences. The established cell line was responsive to environmental variables, reflecting in vivo observations. Thus, it was possible to present a set of resources (standard karyotype, centromeric marker, draft genome, mitogenome, and cell line) and their applications and relevance in ecotoxicology. The toolkit should contribute to further studies on the response of organisms to the natural conditions of the Amazon and the impacts that this region has been receiving.
Keywords: Amazon; cell culture; ecotoxicology; fish; genome